PENGARUH KATALIS NaOH PADA PROSES ISOLASI LIGNIN DARI TANDAN KOSONG KELAPA SAWIT - Masdayani Rambe, Andi Nata, Netti Herlina (Jurnal Teknik Kimia USU, 2013)
Oil palm empty fruit bunches (TKKS) is one of the solid waste generated by the palm oil industry that contain lot of fibers. Based from its chemical composition, TKKS has the potential to be used as a source of chemicals that lignin. Lignin can be used commercially as binders, adhesives, fillers, surfactants, polymer products, dispersants and other chemicals. This study used fiber powder TKKS cleared of extractive substances to extract them using benzene: 96% ethanol (2:1, v / v) for 6 hours. Fiber powder is then cooked with a variety of cooking 1,2,3 hours with the addition of NaOH variation of 10%, 15%, and 20% to obtain the black liquor, black liquor and dilution variations during lignin isolation. The results showed that the optimum yield of lignin obtained is 16.42% with 84.21% purity lignin in cooking 2 hour treatment with the addition of 20% NaOH and diluting the black liquor 1:2. The test results showed FT-IR has wavelengths lignin constituent functional groups in according with the standard lignin. Keywords: oil palm empty fruit bunches,TKKS, lignin, lignin isolated